Foot Gel Mask from Aloe Vera Leaf Flesh (Aloe vera (L.) Burm.f.): Formulation and Evaluation - Nurfadilla, Kiki; Lubis, Minda Sari; Dalimunthe, Gabena Indrayani; Yuniarti, Rafita (Pustaka Media Publishing, 2024)
Formulation and evaluation of a gel foot mask preparation from aloe vera leaf flesh (Aloe vera (L.) Burm.f.) have been carried out. The secondary metabolite content of aloe vera leaf flesh was identified through phytochemical screening. The formulation of the gel foot mask was carried out by varying the concentration of aloe vera leaf flesh by 2.5%, 5%, and 10%. Evaluation of the physical quality of the gel mask preparation included organoleptic, homogeneity, pH of the preparation, spreadability, adhesiveness, drying time of the preparation, viscosity, and exfoliation test. The results of phytochemical screening showed that aloe vera leaf flesh contains flavonoids, glycosides, tannins, saponins, and steroids. Evaluation of physical quality showed that the gel mask has characteristics and meets the standards of a good gel mask preparation. The exfoliation test of the gel mask showed a good effect on the skin, namely increased skin moisture and good skin elasticity after using a gel foot mask from aloe vera leaf flesh with an effective increase in the 10% formulation. The higher the concentration of the preparation, the better the exfoliator effectiveness.